P071 Cancer preventive effect of recombinant TRAIL by ablation of oncogenic inflammation in colitis-associated cancer rather than anticancer effect. (16th January 2018) - Hahm, K B; Park, J M; Han, Y M; Hong, S; Lee, K C
Abstract: Background: The potential of tumour necrosis factor-related apoptosis-inducing ligand (TRAIL) in inducing apoptosis is a hallmark in cancer therapeutics, after which its selective ability to achieve cell death pathways against cancer cells led to hope for recombinant TRAIL in cancer therapeutics. Methods: The present data from azoxymethane-initiated, dextran sulfate sodium-promoted colitis-associated cancer (CAC) model strongly indicate the potential of rTRAIL in cancer prevention rather than in cancer therapeutics. Results: Early treatment of rTRAIL significantly reduced colitis and CAC by inhibiting the recruitment of macrophages into the damaged mucosa and activating the scavenger activity with efferocytosis and the production of several growth factors. In contrast, late administration of rTRAIL as for anti-cancer effect did not decrease the initiation and development of CAC at all. Significant cancer preventing mechanisms of rTRAIL were identified. In the CAC model, anti-inflammation, regeneration, and efferocytosis was induced by treatment of TRAIL for 6 days, significant inhibitory activity was evident at 4 weeks and anti-oxidative and anti-inflammatory induction were noted at 12 weeks. Most importantly, TRAIL promoted tissue regeneration by enhancing the resolution of pathological inflammation through the activation of the NLRP3 inflammasome pathway. The results indicate that TRAIL reduces the induction of colitis and the initiation of CAC by inhibiting pro-inflammatory signalling and promoting tissue repair to maintain intestinal homeostasis through activation of the NLRP3 inflammasome. Conclusions: Therefore, TRAIL can be used as a chemopreventive agent against CAC, rather than as a therapeutic drug endowing apoptosis.